EBASIM: un espectrógrafo sobre banco óptico para CASLEO - Simmons, Jorge Enrique (1994)
We have made the preliminary design of a bench echelle to be installed at the 2.1 m telescope located at the national observing facility in Argentina. We have chosen a design which uses the echelle grating with the grooves parallel to the optical bench. The angle between the camera and the colimator is 12° and the cross disperser will work in a quasi-Littrow mode.